Cyber ​​Preaching Management and Public Opinion Formation Strategies on the Twitter Platform - Sukirno, Sukirno; Roa'zah, Nandipah; Muazaroh, Muslimatun Diana; Afifah, Diana Elfiyatul; Nuruzzaman, Moh. Agil; Supeno, Supeno; Munahar, Munahar; Fitria, Yuni Rohma (Westscience Press, 2024)
The development of social media has significantly changed the landscape of da'wah, particularly through the presence of the Twitter platform, which has become a fast, interactive, and algorithmic public discourse space. This study aims to analyze how cyber da'wah management is implemented by da'wah accounts on the Twitter platform and how their communication strategies contribute to the formation of public opinion. Using a qualitative approach with a multiple case study design, this study examined three da'wah accounts selected purposively based on their level of activity, influence, and audience engagement. Data were collected through passive netnography over three months, analysis of digital documents, visual artifacts, and supporting literature studies. Analysis was conducted using Miles and Huberman's interactive model through data reduction, data presentation, and cross-case verification. The results show that effective cyber da'wah combines moment-based content planning, digital identity organization, utilization of platform features such as hashtags, threads, and trending topics, and evaluation based on interaction metrics. The communication strategies used include framing messages according to the social context, building credibility as micro-influencers, and strengthening communality through two-way interactions. Public opinion formation occurs through a combination of persuasive framing, the presence of credible influencers, and audience participation in digital dialogue. The study also identified supporting factors such as an intuitive understanding of platform algorithms and audience spiritual needs, as well as a number of challenges such as discourse polarization, competition for attention (attention economy), and the risk of misinformation. This study offers an integrative model of cyber da'wah management that combines classical management principles, digital communication strategies, and platform logic. These findings provide theoretical contributions to the study of digital da'wah and practical recommendations for da'wah managers to design effective, data-driven, and adaptive content strategies to the dynamics of the digital space.